2020
DOI: 10.3390/catal10080813
|View full text |Cite
|
Sign up to set email alerts
|

CoMn Catalysts Derived from Hydrotalcite-Like Precursors for Direct Conversion of Syngas to Fuel Range Hydrocarbons

Abstract: Two different groups of CoMn catalysts derived from hydrotalcite-like precursors were prepared through the co-precipitation method, and their performance in the direct production of gasoline and jet fuel range hydrocarbons through Fischer–Tropsch (FT) synthesis was evaluated in a batch autoclave reactor at 240 °C and 7 MPa and H2/CO of 2. The physicochemical properties of the prepared catalysts were investigated and characterized using different characterization techniques. Catalyst performance was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In 2009, the American Society for Testing Materials issued its inaugural approval for aviation kerosene produced using the FTJ method for use in commercial flights [10]. The Fischer-Tropsch (FT) process converts syngas, consisting of CO and H 2 , into alkane fuels [11]. Catalysts are pivotal in FT synthesis, commonly employing Fe, Co, Ni, and Ru [12].…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, the American Society for Testing Materials issued its inaugural approval for aviation kerosene produced using the FTJ method for use in commercial flights [10]. The Fischer-Tropsch (FT) process converts syngas, consisting of CO and H 2 , into alkane fuels [11]. Catalysts are pivotal in FT synthesis, commonly employing Fe, Co, Ni, and Ru [12].…”
Section: Introductionmentioning
confidence: 99%
“…In such a sense, authors [7] have demonstrated the substitution of La with K cations in LaNiO 3 perovskite that exhibited a 100% selectivity towards the methanation of CO 2 at all temperatures investigated. On the other hand, reducing CO to value-added products such as gasoline and jet fuel range hydrocarbons by two different groups of CoMn catalysts derived from hydrotalcite-like precursors was reported by Gholami et al [8]. The catalysts prepared using a KOH + K 2 CO 3 mixture as a precipitant agent exhibited a high selectivity of 51-61% for gasoline (C 5 -C 10 ) and 30-50% for jet fuel (C 8 -C 16 ) range hydrocarbons compared with catalysts precipitated by KOH.…”
mentioning
confidence: 96%